Цэвээнравдан хунтайж Зүүн гар улсын хаан суусан нь - Саруул, И. (Historia Mongolarum, 2003)
This article touched the issues related with Mongolian Zuun Gar Khanate and political activities of the Tseveenravdan. At that times in Zuun Gar Khanate were at political crisis. However, Tseveenravdan khutagtu managed to stabilize the situation and became the khaan.